Serological Biomarkers in Early Axial Spondyloarthritis During 24-Months Follow Up (Italian Arm of Space Study) - Lorenzin, Mariagrazia; Ortolan, Augusta; Felicetti, Mara; Favero, Marta; Vio, Stefania; Zaninotto, Martina; Polito, Pamela; Cosma, Chiara; Scapin, Vanna; Lacognata, Carmelo; Ramonda, Roberta (Frontiers in Medicine, 2019)
Objectives: The study aimed to evaluate biomarkers facilitating early axial-spondyloarthritis (axSpA) diagnosis and disease activity and imaging indices correlated. Materials and Methods: Seventy-five patients with low back pain (≥3 months,≤2 years,onset ≤45 years) participating in the Italian arm of the SpondyloArthritis-Caught-Early (SPACE) study underwent a physical examination, questionnaires, laboratory tests, spine and sacroiliac joints (SIJ) X-rays and MRI at baseline and during a 24-months follow-up. Two expert rheumatologists formulated axSpA diagnosis and assessed fulfilment of ASAS criteria. Disease activity and physical functioning were assessed using imaging, clinical and serological indices. Spine and SIJ MRI and X-rays were scored independently by 2 readers following the SPARCC, mSASSS and NY-criteria. Patients were classified in accordance to ASAS criteria as:21 patients classified according to axSpA imaging-arm;29 patients classified according to axSpA clinical±imaging arm;25 patients not fulfilling ASAS criteria. Results: At baseline biomarker levels were not significantly increased in any of the patient groups. Instead, a significant decrease of all functional and disease activity indices from baseline to 24 months was observed in all the three groups. In the same period, there were no significant variation in the serological markers values within each group.The correlations between IL-17 and IL-23 and clinical and functional indices were not significant. On the other hand, significant correlations were found between IL-22 and BASFI, BASG1, HAQ, VAS pain; MMP3 and mSASSS;MMP3 and hsCRP. Conclusions: Although not significantly higher in any of the cohorts, IL-22, MMP3 and hsCRP values correlated with some disease activity indices and with mSASSS. Further studies are warranted to confirm these preliminary findings.